2009
DOI: 10.1016/j.echo.2009.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Interatrial Conduction Time and Left Atrial Function in Patients With Left Ventricular Systolic Dysfunction: Effects of Cardiac Resynchronization Therapy

Abstract: Background-Prolonged inter-atrial conduction time (IACT) can be associated with abnormal left atrial (LA) function but has not been characterized in patients with left ventricular systolic dysfunction (LVSD) and a QRS interval >130 ms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…The increase in LA L L EMC and IA I I EMC found in the elderly group was due to the evident prolongation measured in lateral PA P P , despite the lack of detectable changes in tricuspid PA P P and septal PA P P . This result l l is consistent wi w w th the report of Waggoner et al, who demonstrated a delay in lateral PA in patients with heart failure in correlation with LA volume (20).…”
supporting
confidence: 91%
“…The increase in LA L L EMC and IA I I EMC found in the elderly group was due to the evident prolongation measured in lateral PA P P , despite the lack of detectable changes in tricuspid PA P P and septal PA P P . This result l l is consistent wi w w th the report of Waggoner et al, who demonstrated a delay in lateral PA in patients with heart failure in correlation with LA volume (20).…”
supporting
confidence: 91%
“…A prolonged PR interval is often considered detrimental to diastolic filling because it leads to a decrease in diastolic filling time. However, patients with a prolonged PR interval often have delayed interatrial conduction times 22 and thus may benefit from a longer PR interval because it may allow for complete atrial emptying during atrial systole. Thus, the interaction between a prolonged PR, CRT, diastolic filling, and outcomes, is likely complex, depending, at least in part, on atrial conduction times and the programmed AV delay.…”
Section: Discussionmentioning
confidence: 99%
“…Interatrial conduction abnormality was shown to be present by tissue Doppler echocardiography in patients with heart failure due to left ventricular systolic dysfunction [25]. Prolonged interatrial conduction time in patients with severe left ventricular systolic dysfunction can affect left atrial remodeling and function [26]. Can et al [27] evaluated interatrial conduction in patients with scleroderma with the same method.…”
Section: Discussionmentioning
confidence: 99%